Antiparasitic Activity of Oxindolimine–Metal Complexes against Chagas Disease - Marcelo Cecconi Portes; Grazielle Alves Ribeiro; Gustavo Levendoski Sabino; Ricardo Alexandre Alves De Couto; Leda Quércia Vieira; Maria Júlia Manso Alves; Ana Maria Da Costa Ferreira (Inorganics, 2023)
Some copper(II) and zinc(II) complexes with oxindolimine ligands were tested regarding their trypanocidal properties. These complexes have already shown good biological activity in the inhibition of tumor cell proliferation, having DNA and mitochondria as main targets, through an oxidative mechanism, and inducing apoptosis. Herein, we demonstrate that they also have significant activity against the infective trypomastigote forms and the intracellular amastigote forms of T. cruzi, modulated by the metal ion as well as by the oxindolimine ligand. Selective indexes (LC50/IC50) determined for both zinc(II) and copper(II) complexes, are higher after 24 or 48 h incubation with trypomastigotes, in comparison to traditional drugs used in clinics, such as benznidazole, and other metal-based compounds previously reported in the literature. Additionally, tests against amastigotes indicated infection index <10% (% of infected macrophages/average number of amastigotes per macrophage), after 24 or 48 h in the presence of zinc(II) (60–80 µM) or analogous copper(II) complexes (10–25 µM). The copper complexes exhibit further oxidative properties, being able to damage DNA, proteins and carbohydrates, in the presence of hydrogen peroxide, with the generation of hydroxyl radicals. This redox reactivity could explain its better performance towards the parasites in relation to the zinc analogs. However, both copper and zinc complexes display good selective indexes, indicating that the influence of the ligand is also crucial, and is probably related to the inhibition of some crucial proteins.